#BLACKLIVESMATTER and struggle over national discourse on Twitter: digital activism as new public sphere - Bondarenko, Valeria; Kaptiurova, Olena; Orlova, Vira (Current issues of Ukrainian linguistics: theory and practice, 2021)
The tragic death of George Floyd, an African-American male killed by a white policeman, has been widely discussed on social media and instigated many to use social media as an argumentum over the law enforcement role and the racist status quo in the USA. As social media have unignorably become a tool for activists who seek to introduce new voices into the present-day monoglossic public opinion, Twitter has offered the space for the Black Lives Matter digital activism to create their own identity that enables them to participate in (re)shaping the public opinion and aspire for social change. Social media, leaning on the technological thrust into modern society, have created a viable substitute for public sphere to challenge the power and hegemony which control the production of discourse and agenda that dominate the public opinion. The study draws on Habermas' theory of the 'public sphere' so as to conceptualize the #BalckLivesMatter (BLM) activism aimed at controlling the public national discourse. Critical Discourse Analysis, in its turn, provides the framework for critical examination of language choices and the ways in which texts are structured, selected, and invested with meanings that facilitate the promotion of certain ideologies and particular social representations. Using this theoretical background, the article explores language means used in Twitter messages (http://twitter.com) by BLM activists between May 25 and 31, 2020, in the aftermath of Floyd's death. The article reveals that #BlackLivesMatter tweets expose the discourse of inequality, injustice and racism across the American nation and that Twitter is used by the black minority marginalized in the American society as an alternative space to (re)construct the public sphere and to challenge the mainstream mass media dominated by the white ideology. The linguistic analysis uncovers the divisive nature of #BlackLivesMatter messages on Twitter expressed by the emphatic blacks vs whites opposition as well as their particularism that becomes pronounced in the debates of BLM activists with the universalist #AllLivesMatter supporters.
Keywords: digital activism, public sphere, #BlackLivesMatter, Twitter, public discourse, critical discourse analysis.